Evaluating different plant extracts against three major diseases of mulberry - and B. SARATCHANDRA, SUBRATA BISWAS*. N.K. DAS, S.M.H. QADRI (Indian Phytopathology, 2002)
The effects of 10% alcoholic water extracts of fresh plant parts from 20 different species were investigated on the development of powdery mildew (Phyllactinia corylea) leaf spot (Pseudocercospora mori) and leaf rust (Cerotelium fici) of mulberry during 1992-93 and 1993-94 in West Bengal, India. The pooled data of these 2 years revealed that the extract of Adhatoda zeylanica was most effective in decreasing the severity of all the diseases followed by extracts of Azadirachta indica, Launaea coromandelica [Lannea coromandelica] and Oxalis corniculata which significantly minimized powdery mildew and leaf rust, while those of Celosia argentia and Chromolaena odorata reduced leaf spot and leaf rust. Extracts from several other plant species exhibitedan ability to reduce either leaf rust or powdery mildew disease.